2006
DOI: 10.1196/annals.1362.031
|View full text |Cite
|
Sign up to set email alerts
|

Flow Rate Limitation in Open Capillary Channel Flows

Abstract: This paper reports the experimental and theoretical investigations of forced liquid flows through open capillary channels under reduced gravity conditions. An open capillary channel is a structure that establishes a liquid flow path at low Bond numbers, when the capillary pressure caused by the surface tension force dominates in comparison to the hydrostatic pressure induced by gravitational or residual accelerations. In case of steady flow through the channel, the capillary pressure of the free surface balanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…The cross section of the flow also evolves along the flow and can be calculated versus k(x), the distance of the free surface to the mid-plan of the channel (z = 0). Following Haake et al (2006), two situations can be observed. The liquid can be pinned at the edge of the channel when k > (b À a)/ 2, or the liquid separates from the edge of the channel when k < (b À a)/2.…”
Section: Mean Bubble Velocity and Void Fractionmentioning
confidence: 95%
See 1 more Smart Citation
“…The cross section of the flow also evolves along the flow and can be calculated versus k(x), the distance of the free surface to the mid-plan of the channel (z = 0). Following Haake et al (2006), two situations can be observed. The liquid can be pinned at the edge of the channel when k > (b À a)/ 2, or the liquid separates from the edge of the channel when k < (b À a)/2.…”
Section: Mean Bubble Velocity and Void Fractionmentioning
confidence: 95%
“…The hydrodynamics and the stability of forced flows in open capillary channels were investigated by Rosendahl et al (2001Rosendahl et al ( , 2004, Haake et al (2006), Rosendahl and Dreyer (2007), Grah et al (2008). For an internal liquid pressure lower than ambient gas pressure the free liquid surface is bent inwards and concave at any cross section.…”
Section: Introductionmentioning
confidence: 99%
“…The forced liquid flow through open capillary channels was investigated experimentally, theoretically and numerically by Rosendahl et al (2004), Haake et al (2006), Rosendahl and Dreyer (2007), Grah et al (2008). It was found that for an internal liquid pressure lower than ambient gas pressure, the free liquid surface is bent inwards and concave at any cross section.…”
Section: State Of Artmentioning
confidence: 99%
“…Again, if a constant radius at the mean curvature plane for R 1 is assumed, the principal radius of surface curvature R 1 is a function of k only (Haake et al 2006). …”
Section: Governing Equationsmentioning
confidence: 99%
“…Therefore the cross-section area is a function of the minimal contour value k, one of the main variables of the following differential equation system. The detailed derivation of the governing equation for A(k) can be found in Haake et al (2006). The convective term of the Bernoulli equation (7) can be rewritten as…”
Section: Governing Equationsmentioning
confidence: 99%